Field Efficacy of Seed Dressing Fungicides on Emergence, Survival and Seedling Vigour of Sunnhemp (Crotalaria juncea L.) - S.K. SARKAR; S.C. SAXENA (Seed Research, 2026)
Five seed treating fungicides namely Apron, Divident, Mancozeb, Thiram and Bavistin were evaluated in four sunnhemp varieties namely K-12 yellow, K-12 black, Chindwara and T-6 for field emergence, survival and seedling vigour under field condition at GBPUA&T, Pantnagar. The best results in increasing survival percentage of seedling were recorded in Thiram or Mancozeb treated seed of all the varieties. Field emergence and seedling vigour were also significantly higher in Thiram treated seed.